The Italian financial system in the perspective of 1992 - L. DINI (PSL Quarterly Review, 2013)
The work focuses on the Italian financial system, which, in the perspective of the completion of the Single European Market, must catch up with the more developed markets. The tasks to be achieved are formidable and many questions are still open. The great vision of the 1992 project requires - and deserves - a great deal of work if it is to be realised, especially in the financial field. The author analyses the problems of regulation and supervision of financial activities at the European level, the development of the Italian financial system and the need for further structural changes.